Behavior and modeling of RC beams subjected to high rates of concentrated loading - Song, Jia Yun. (2011)
During recent decades, the increasing amount of accidents such as earthquakes, blasting, terrorist attack attracted lot researchers to analyze and design the reinforced concrete structures against these accidents. However, the knowledge and studies of this area is still not enough to deal with the accurate prediction of these problems. Beams are the key load bearing elements in frame structures in which beam failure will probably trigger a progressive collapse.The limitation on three dimensional nonlinear finite element analyses of the dynamic response of reinforced concrete beams is the main purpose of this research. The objective of this research is to study the dynamic response of the reinforced concrete beams under high rate concentrated load. LS-DYNA is a nonlinear finite element analysis program which is used to model the numerical simulations. The LS-DYNA model was subjected to simulated high rate concentrated loads and investigations were carried out on the dynamic response and material capacities of the beams.